Nutritional assessment of shift workers - Zacharewicz, Kamila; Kucharska, Alicja; Sińska, Beata (Polish Journal of Public Health, 2012)
Introduction. Shift work may contribute to increased risk of developing many diseases and ailments. Different from normal work schedule affects many aspects of life, including nutritional pattern. Aim. The aim of this study was to analyse the impact of shift work on nutrition. Material and methods. The study group consisted of 35 emergency medical technicians at the age of 19-60, working in medical emergency departments in Warsaw and surrounding areas. A questionnaire was used to analyse nutritional changes while in the quantitative evaluation of nutrition a 2-day food record was used. Results. Assessment of nutrition of the studied group showed a number of irregularities. Paramedics’ diets were characterized by excessive consumption of saturated fatty acids and high atherogenic quotient. There was also insufficient intake of dietary fiber and B vitamins. In women’s diets there was also an insufficient content of potassium, iron and foliate. The main determinants of inappropriate feeding were lack of time and irregular meals. Conclusions. Nutrition patterns of the test group deviate significantly from the principles of proper nutrition, and they have been affected adversely by working in shifts.